Human Umbilical Cord Mesenchymal Stem Cells: Subpopulations and Their Difference in Cell Biology and Effects on Retinal Degeneration in RCS Rats - Wang, L.; Li, P.; Tian, Y.; Li, Z.; Lian, C.; Ou, Q.; Jin, C.; Gao, F.; Xu, J.-Y.; Wang, J.; Wang, F.; Zhang, J.; et al. (Current Molecular Medicine, 2017)
Background: Human umbilical cord mesenchymal stem cells (hUC-MSCs) are potential candidates for treating retinal degeneration (RD). Objective: To further study the biology and therapeutic effects of the hUC-MSCs on retinal degeneration. Methods: Two hUC-MSC subpopulations, termed hUC-MSC1 and hUC-MSC2, were isolated by single-cell cloning method and their therapeutic functions were compared in RCS rat, a RD model. Results: Although both subsets satisfied the basic requirements for hUC-MSCs, they were significantly different in morphology, proliferation rate, differentiation capacity, phenotype and gene expression. Furthermore, only the smaller, fibroblast-like, faster growing subset hUC-MSC1 displayed stronger colony forming potential as well as adipogenic and osteogenic differentiation capacities. When the two subsets were respectively transplanted into the subretinal spaces of RCS rats, both subsets survived, but only hUC-MSC1 expressed RPE cell markers Bestrophin and RPE65. More importantly, hUC-MSC1 showed stronger rescue effect on the retinal function as indicated by the higher b-wave amplitude on ERG examination, thicker retinal nuclear layer, and decreased apoptotic photoreceptors. When both subsets were treated with interleukin-6, mimicking the inflammatory environment when the cells were transplanted into the eyes with degenerated retina, hUC-MSC1 expressed much higher levels of trophic factors in comparison with hUC-MSC2. Conclusion: The data here, in addition to prove the heterogeneity of hUC-MSCs, confirmed that the stronger therapeutic effects of hUC-MSC1 were attributed to its stronger anti-apoptotic effect, paracrine of trophic factors and potential RPE cell differentiation capacity. Thus, the subset hUC-MSC1, not the other subset or the ungrouped hUC-MSCs should be used for effective treatment of RD.
Keywords: cell differentiation